Defects Passivation for Perovskite Solar Cells: Bulk Passivation and Interfacial Passivation for Perovskite Solar Cells: Which One is More Effective? (Adv. Mater. Interfaces 9/2021). Issue 9 (7th May 2021) - Wang, Jintao; Jin, Guangyong; Zhen, Qingzhu; He, Chenyang; Duan, Yu
Abstract : The harsh environment during the voyage is a challenge for every power system. This is also a challenge for the sailing boats powered by perovskite solar cells (PSCs). In article number 2002078, Guangyong Jin, Yu Duan, and co‐workers review the defects passivation for PSCs. It is expected that with the effective passivation strategy and the powerful encapsulation, the commercialization for PSCs could be realized even under the extreme application scenarios.